An emerging role for misfolded wild-type SOD1 in sporadic ALS pathogenesis - Rotunno, Melissa S.; Bosco, Daryl A. (Frontiers in Cellular Neuroscience, 2013)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder that targets motor neurons, leading to paralysis and death within a few years of disease onset. While several genes have been linked to the inheritable, or familial, form of ALS, much less is known about the cause(s) of sporadic ALS, which accounts for approximately 90% of ALS cases. Due to the clinical similarities between familial and sporadic ALS, it is plausible that both forms of the disease converge on a common pathway and, therefore, involve common factors. Recent evidence suggests the Cu,Zn-superoxide dismutase (SOD1) protein to be one such factor that is common to both sporadic and familial ALS. In 1993, mutations were uncovered in SOD1 that represent the first known genetic cause of familial ALS. While the exact mechanism of mutant-SOD1 toxicity is still not known today, most evidence points to a gain of toxic function that stems, at least in part, from the propensity of this protein to misfold. In the wild-type SOD1 protein, non-genetic perturbations such as metal depletion, disruption of the quaternary structure, and oxidation, can also induce SOD1 to misfold. In fact, these aforementioned post-translational modifications cause wild-type SOD1 to adopt a “toxic conformation” that is similar to familial ALS-linked SOD1 variants. These observations, together with the detection of misfolded wild-type SOD1 within human post-mortem sporadic ALS samples, have been used to support the controversial hypothesis that misfolded forms of wild-type SOD1 contribute to sporadic ALS pathogenesis. In this review, we present data from the literature that both support and contradict this hypothesis. We also discuss SOD1 as a potential therapeutic target for both familial and sporadic ALS.